Improvement of the SOD activity of the Cu2+ complexes by hybridization with lysozyme and its hydrogen bond effect on the activity enhancement - Nakane, Daisuke; Akiyama, Yukihito; Suzuki, Soma; Miyazaki, Ryotaro; Akitsu, Takashiro (Frontiers in Chemistry, 2024)
We prepared L-amino acids (L-valine and L-serine, respectively) based on the Schiff base Cu 2+ complexes CuSV and CuSS in the absence/presence of hydroxyl groups and their imidazole-bound compounds CuSV-Imi and CuSS-Imi to reveal the effects of hydroxyl groups on SOD activity. The structural and spectroscopic features of the Cu 2+ complexes were evaluated using X-ray crystallography, UV-vis spectroscopy, and EPR spectroscopy. The spectroscopic behavior upon addition of lysozyme indicated that both CuSV and CuSS were coordinated by the imidazole group of His15 in lysozyme at their equatorial position, leading to the formation of hybrid proteins with lysozyme. CuSS-Imi showed a higher SOD activity than CuSV-Imi, indicating that the hydroxyl group of CuSS-Imi played an important role in the disproportionation of O2 -ion. Hybridization of the Cu 2+ complexes CuSV and CuSS with lysozyme resulted in higher SOD activity than that of CuSV-Imi and CuSS-Imi. The improvements in SOD activity suggest that there are cooperative effects between Cu 2+ complexes and lysozyme.